Green IT: Reduce your information system's environmental impact while adding to the bottom line - Velte Toby J. (MC Graw Hill, 2008)
This groundbreaking work offers a complete roadmap for integrating environmentally sound techniques and technologies into your Information Systems architecture. Green IT explains how to adopt a business-driven green initiative and provides a detailed implementation plan. You will find strategies for reducing power needs, procuring energy from alternative sources, utilizing virtualization technologies, and managing sustainable development. Case studies highlighting successful green IT projects at major organizations are included. Keep your IT department and your organization in the green--both environmentally and financially--with help from this comprehensive guide.